Turkish national wrestlers and halal food-related problems in the organization of international sport. - Soygüden, A.; Taskiran, C. (International Journal of Wrestling Science, 2019)
The study was carried out in order to determine the halal food problems that the members of the Turkish national wrestling team have experienced at the international sports organizations held abroad. National wrestlers are affected psychologically and motivationally in sports performances due to the absence of halal food. This study aims to draw attention to halal food in international the organization of sports. Materials and Methods: a questionnaire form was prepared by the researchers and used in the study. There are 12 questions in the questionnaire including 8 halal food questions and 4 socio-demographic questions. The questions in the questionnaire were prepared in consultation with academicians working at different universities. The study of the different age groups (n = 40) were applied to the old and the new Turkish national wrestling team members. As a result of the questionnaire survey, the data were entered into the SPSS program and statistical percentages were obtained. Results: in the study 100% of the national wrestlers participating in the study were male athletes and 45% of the athletes participating in the study were ages between 21-25 years old. In the study, 85% of the participants were university graduates. In the survey, 70% of the national wrestlers who participated to the study were stated that they participated in international sport organizations between 1-5 times and 22.5% between 6-10 times. In the study, 95% of the national wrestlers who participated in the survey responded "No" to the Question: Can you easily consume the food at the accommodation place in the sports competitions held abroad?". In the study, 100% of the athletes participating in the study answered "yes" to the question: Are you paying attention to the halal food when going on in sports competitions abroad?". In the study, 80% of the athletes responded "yes" to the question: Does it affect your sport performance because there is no halal food abroad?". In the study 92.5% of the athletes answered "yes" to the question "Are you bringing halal food with you in sports competitions made abroad?". In the study, participant`s food consumption was declared by the athletes, 90% vegetable, 87.5% fruit, 85% pilaf (rice), 65% chicken, 60% fish, 32.5% pasta and nuts, and only 2.5% red meat. Conclusion; we see that athlete`s sports performance, psychological and motivational is effected among national wrestlers abroad due to the absence of halal food or lack of halal food preparation process. It is recommended that international sports federations conduct studies on halal food in sport organizations held abroad. Competition on equal terms for all athletes will contribute to better levels of world sport.